2022
DOI: 10.1007/s11156-022-01099-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing stock market anomalies with machine learning

Abstract: We examine the predictability of 299 capital market anomalies enhanced by 30 machine learning approaches and over 250 models in a dataset with more than 500 million firm-month anomaly observations. We find significant monthly (out-of-sample) returns of around 1.8–2.0%, and over 80% of the models yield returns equal to or larger than our linearly constructed baseline factor. For the best performing models, the risk-adjusted returns are significant across alternative asset pricing models, considering transaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 90 publications
(105 reference statements)
1
12
0
Order By: Relevance
“…Some market anomalies occur only once and then disappear, while others sometimes occur continuously or frequently (Tversky & Kahneman, 1986). Market anomalies can also happen in a non-standardized market environment (Azevedo & Hoegner, 2023). Previous studies have shown anomalies exist in the U.S. and other countries (Salur & Ekinci, 2023).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Some market anomalies occur only once and then disappear, while others sometimes occur continuously or frequently (Tversky & Kahneman, 1986). Market anomalies can also happen in a non-standardized market environment (Azevedo & Hoegner, 2023). Previous studies have shown anomalies exist in the U.S. and other countries (Salur & Ekinci, 2023).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Inefficiency is related to human behavior that leads to irrationally (Azevedo & Hoegner, 2023;Musnadi & Majid, 2018). Therefore, financial behavior can explain financial inefficiencies, such as market anomalies (Hudson & Muradoglu, 2020).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying complex stock market patterns requires intricate techniques, with feature selection being pivotal for robust predictions, as features unveil crucial insights from intricate data [3]. In their 2023 research, Vitor Azevedo et al investigated the prediction of capital market anomalies, using diverse machine learning techniques and models on a massive dataset, with top models showing significant monthly returns of 1.8% to 2.0% [4]. The authors investigate ANN, SVM, and LSTM neural networks, highlighting their distinct characteristics and practical applications, underscoring the transformative role of machine learning in shaping investment strategies [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to such inconsistency, Scholars started to apply non-linear techniques such as machine learning technologies to enhance anomalies. Empirical results show those results have further been enhanced by applying a diverse set of machine learning approaches 9,10 .…”
Section: Introductionmentioning
confidence: 99%